HUBUNGAN TINGKAT KECEMASAN TERHADAP KUNJUNGAN LANSIA KE PELAYANAN KESEHATAN PADA MASA PENDEMI COVID-19 - Ridho Kurniawan; Arneliwati Arneliwati; Reni Zulfitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Elderly is someone who has entered the age of 60 and over which is very vulnerable to experiencing anxiety which is influenced by various factors. The purpose of this study was to determine the relationship between anxiety levels and elderly visits to health services during the Covid-19 pandemic. This study used a cross sectional approach. The number of samples used in this study were 73 people who were taken using purposive sampling technique. The data collection was taken using the GAD-7 (Generalized Anxiety Disorder-7) questionnaire and the elderly visit questionnaire to health services where the anxiety questionnaire has been modified and has been tested for validity and reliability. Analysis of the data used is univariate and bivariate using the Chi-Square test. The results showed that the description of the level of anxiety in the elderly was mostly mild (63.0%). The majority of elderly visits to health services choose to keep visiting during the Covid-19 pandemic (90.4%). Bivariate analysis showed that p-value (0.224) > (0.05) where there was no significant relationship between anxiety levels and elderly visits to health services during the Covid-19 pandemic in the work area of the Sidomulyo Outpatient Health Center. The results of this study found that the level of anxiety experienced by the elderly due to the current pandemic did not affect the elderly to visit or not visit health services.Keywords : Covid-19; anxiety; visits to health service; elderly.